EFFICACY OF DIFFERENT GROUPS OF INSECTICIDES AGAINST DUSKY COTTON BUG, OXYCARENUS LAETUS KIRBY IN FIELD CONDITIONS OF PAKISTAN - Ali Shah, Syed Ishfaq; Jan, Muhammad Tahir; Rafiq, Muhammad; Malik, Tassawar Hussain; Khan, Imran Rafi; Hussain, Zahid (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
To assess the efficacy against dusky cotton bug (Oxycarenus laetus) in field conditions, a total of 12 insecticides belonging to five different groups viz. ganophosphate, Pyrethroid, Neonicotinoid, Naturalyte and Insect Growth Regulator (IGRs) were tested at the Central Cotton Research Institute, Multan, Pakistan during 2014. Percent mortality was recorded after 24 and 72 hours of application. All tested insecticides were significantly different in relation to pest mortality than untreated check, while mortality ranged from 12.5 to 85.0% and 60.0 to 100%respectively after 24 and 72 hours of the application. Among the insecticides, Triazophos proved most effective and gave 85% mortality followed by Imidacloprid (79.2%), Profenofos (78.0%) and Dimethoate (75.0%) while Spinosad gave lowest pest mortality (12.5%) followed byEmamactin (16.7%), Pyriproxifen (25.0%) and Diafenthiuron (30.0%) after 24 hours of application. Efficacy of all the insecticides increased after 72 hours of the application and they gave 100% mortality except Pyriproxyfen (60.0%), Emamectin (62.5%), Diafenthiuron (80%) and Spinosad (83.3%). In untreated check 3.8 and 8.4% pest mortality was recorded respectively after 24 and 72 hours of application. Among the different insecticidal groups, Organophosphates proved most effective and gave 79.3% pest mortality followed by Pyrethroids (53.6%) and Neonicotinoids (53.4%) while Naturalite proved least effective and gave 14.6% mortality followed by Insect Growth Regulator (IGRs) (25.0%) after 24 hours of the application. Whereas, Organophosphates and Pyrethroids gave 100% pest mortality 72 hours of application followed by Neo-nicotinoids (93.3%) while, IGRs and Necotinoids proved least effective and gave 60.0 and 72.9% pest mortality respectively.